The Impact of Ageing on the CNS Immune Response in Alzheimer’s Disease - Chee, Stephan En Jie; Solito, Egle (Frontiers in Immunology, 2021)
Alzheimer’s Disease (AD) is a progressive neurodegenerative disease strongly associated with increasing age. Neuroinflammation and the accumulation of amyloid protein are amongst the hallmarks of this disease and most translational research to date has focused on targeting these two processes. However, the exact etiology of AD remains to be fully elucidated. When compared alongside, the immune response in AD closely resembles the central nervous system (CNS) immune changes seen in elderly individuals. It is possible that AD is a pathological consequence of an aged immune system secondary to chronic stimulation by a previous or ongoing insult. Pathological changes like amyloid accumulation and neuronal cell death may reflect this process of immunosenescence as the CNS immune system fails to maintain homeostasis in the CNS. It is likely that future treatments designed to modulate the aged immune system may prove beneficial in altering the disease course. The development of new tests for appropriate biomarkers would also be essential in screening for patients most likely to benefit from such treatments.